Methicillin resistant Staphylococcus aureus in the United Arab Emirates: a 12-year retrospective analysis of evolving trends - Jens Thomsen; Jens Thomsen; Najiba M. Abdulrazzaq; Najiba M. Abdulrazzaq; The UAE AMR Surveillance Consortium; Godfred Antony Menezes; Carole Ayoub Moubareck; Dean B. Everett; Dean B. Everett; Dean B. Everett; Abiola Senok; Abiola Senok (Frontiers Media S.A., 2023)
IntroductionMethicillin resistant Staphylococcus aureus (MRSA) is a major contributor to the global burden of antimicrobial resistance (AMR). As MRSA continues to evolve, the need for continued surveillance to evaluate trends remains crucial. This study was carried out to assess MRSA trends in the United Arab Emirates (UAE) based on analysis of data from the national AMR surveillance program.MethodsWe carried out a 12-year (2010-2021) retrospective analysis of MRSA demographic and microbiological data collected as part of the UAE national AMR surveillance program. Participating centers from across the country routinely submit AMR surveillance data collected by trained personnel to the National AMR Surveillance Committee, where data is analyzed using a unified WHONET platform. Data on non-duplicate isolates associated with clinical infections were obtained and included in the analysis.ResultsA total of 29,414 non-duplicate MRSA isolates associated with clinical infections were reported between 2010 and 2021 (2010: n = 259; 2021: n = 4,996). MRSA represented 26.4% of all S. aureus (n = 111,623) isolates identified during the study period. In 2010, among the S. aureus isolates with reported oxacillin testing, 21.9% (n/N = 259/1,181) were identified as MRSA and this showed an increase to 33.5% (n/N = 4,996/14,925) in 2021. Although there was variation in the distribution of MRSA across the seven emirates of the country, most had an upward trend. Patient demographics reflected a male preponderance, with most being adults and from the outpatient setting. Isolates were mostly from skin and soft tissue infection specimens (72.5%; n/N = 21,335/29,414). Among the inpatients (N = 8,282), a total of 3,313 MRSA isolates were from specimens obtained ≤ 48 h after admission indicative of community acquired infection. Increasing resistance trends were observed for most antibiotics including ciprofloxacin, levofloxacin, moxifloxacin, erythromycin, gentamicin, trimethoprim-sulfamethoxazole, and quinupristin/dalfopristin. Low levels of resistance (0.0-0.8%) were sustained for linezolid except for 2015, 2016, and 2017 with 2.5, 2.6, and 2.9%, respectively. No confirmed vancomycin resistance was reported.ConclusionThe increasing trend of MRSA isolates associated with clinical infections in the hospital and community settings is a concern. Continued monitoring including incorporation of genomic surveillance and infection control measures are recommended to stem the dissemination.